Front Cover. Issue 7 (17th June 2019) - Lu, Lu; Fritsch, Peter W.; Matzke, Nicholas J.; Wang, Hong; Kron, Kathleen A.; Li, De‐Zhu; Wiens, John J.
Abstract : The cover image is based on the Research Paper Why is fruit colour so variable? Phylogenetic analyses reveal relationships between fruit‐colour evolution, biogeography and diversification by Lu Lu et al., DOI:10.1111/geb.12900 .